Evaluation of Anti-Urolithiatic Activity of Ethanolic Extract of Salacia Reticulata against Ethylene Glycol Induced Urolithiasis in Wistar Albino Rats - Asija, Rajesh; Swami, Amandeep; Sharma, Kanha Ram (Asian Journal of Pharmaceutical Research and Development, 2024)
Urolithiasis is a common disease estimated to affect approximately 12% of the population, with recurrence rates of 70-81% in men and 47-60% in women. It is one of the three most common diseases found in humans. The effects of oral administration of Salacia Reticulata ethanol extract were studied in Wistar rats. Ethylene glycol feeding not only induced hyperoxaluria but also increased renal excretion of serum calcium, creatinine, urea, uric acid, magnesium, and phosphorus. Supplementation with ethanol extract of Salacia Reticulata significantly reduced urinary oxalate, serum uric acid creatinine and increased levels of serum calcium, creatinine, urea, uric acid, magnesium and phosphorus. Increased deposition of stone-forming components in the kidneys of stone-induced rats was also significantly reduced by the ethanol extract of Salacia Reticulata. The results indicate that the ethanolic extract of Salacia Reticulata has anti-urolithiatic activity.